Penegakan Hukum Tindak Pidana Penganiayaan Yang Dilakukan Narapidana Di Lembaga Pemasyarakatan Perempuan Kelas II B Jambi - Badri, Mhd.; Sumaidi, Sumaidi; Iswanto, Reza (Wajah Hukum, 2023)
Prisons are a place to develop prisoners so that when they leave the prison the prisoner will no longer commit a crime. However, in reality, in prisons there have also been criminal acts committed by the prisoners themselves, namely criminal acts of abuse between prisoners. The research method used in this research is using a legal sociology approach with an activity plan for 6 months and the scope of this research is criminal acts committed by prisoners in prison. The materials used in this research are primary legal materials and secondary legal materials. The place used in this research is the Class II B Jambi Correctional Institution. The data collection technique is in the form of interviews and the analysis technique is qualitative analysis. The results of the discussion of this research are that severe disciplinary penalties have not been strictly enforced against inmates who commit criminal acts of abuse and the obstacles are the small number of prison security officers, the lack of interest of prisoners in participating in coaching programs and the facilities and infrastructure which are still limited.